수지 성형품의 제조 방법 - MIZUMA KEITA; SAKAGUCHI HIROYUKI (2024)
본 발명은 성형 다이 메인터넌스용 부재를 성형 다이에 자동적으로 공급할 수 있고, 또한, 성형 다이 메인터넌스용 수지가 성형 다이에 잔류하는 것을 억제 또는 방지 가능한 성형 다이 메인터넌스용 부재를 제공하는 것을 목적으로 한다. 이 목적을 달성하기 위해, 본 발명의 성형 다이 메인터넌스용 부재(10)는, 지지체(11) 및 성형 다이 메인터넌스용 수지(12)를 갖고, 지지체(11)의 적어도 하나의 면 위에 성형 다이 메인터넌스용 수지(12)가 배치되어 있는 것을 특징으로 한다. A method for producing a resin molded product comprises conveying a molding die maintenance member including a plate-like support and a molding die maintenance resin from a common storage to a molding die for resin molding including an upper die and a lower die, clamping the molding die in a state where the molding die maintenance member is placed between the upper die and the lower die of the molding die, performing maintenance by heating the molding die maintenance member after the clamping the molding die, conveying the molding die maintenance member from the molding die, conveying a substrate from the storage to the molding die, and clamping the molding die in a state where the substrate is placed between the upper die and the lower die of the molding die.